The Revival of Quantification: Reflections on Old New Histories. Issue 1 (2021) - Ruggles, Steven
Abstract: Quantitative historical analysis in the United States surged in three distinct waves. The first quantitative wave occurred as part of the "New History" that blossomed in the early twentieth century and disappeared in the 1940s and 1950s with the rise of consensus history. The second wave thrived from the 1960s to the 1980s during the ascendance of the New Economic History, the New Political History, and the New Social History, and died out during the "cultural turn" of the late twentieth century. The third wave of historical quantification—which I call the revival of quantification—emerged in the second decade of the twenty-first century and is still underway. I describe characteristics of each wave and discuss the historiographical context of the ebb and flow of quantification in history.